Varieties of Alternatives Focus Particles and wh-Expressions in Mandarin - Liu, Mingming (Frontiers in Chinese Linguistics,, 2018)
This book concerns two focus particles (jiu, dou) and wh-expressions (shenme = 'what', na geren = 'which person') in Mandarin Chinese. These items are systematically 'ambiguous' and have played important roles in various aspects of Mandarin grammar. An idea based on alternatives and varieties of alternatives in particular - following Chierchia's 2013 analysis of the polarity system - is pursued to account for the systematic ambiguities. The unambiguous semantics of jiu, dou and wh-expressions are maintained and 'ambiguity' explained through varieties of alternatives interacting with other independently motivated aspects of the structure they occur in. By examining these aspects in detail, the book will help readers gain a better understanding of a broad range of phenomena that involve these items - including exhaustivity, distributivity, questions and conditionals.